Karenia brevis allelopathy compromises the lipidome, membrane integrity, and photosynthesis of competitors - Poulin, Remington X. (Sci Rep, 2018)
The formation, propagation, and maintenance of harmful algal blooms are of interest due to their negative effects on marine life and human health. Some bloom-forming algae utilize allelopathy, the release of compounds that inhibit competitors, to exclude other species dependent on a common pool of limiting resources. Allelopathy is hypothesized to affect bloom dynamics and is well established in the red tide dinoflagellate Karenia brevis. K. brevis typically suppresses competitor growth rather than being acutely toxic to other algae. When we investigated the effects of allelopathy on two competitors, Asterionellopsis glacialis and Thalassiosira pseudonana, using nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS)-based metabolomics, we found that the lipidomes of both species were significantly altered. However, A. glacialis maintained a more robust metabolism in response to K. brevis allelopathy whereas T. pseudonana exhibited significant alterations in lipid synthesis, cell membrane integrity, and photosynthesis. Membrane-associated lipids were significantly suppressed for T. pseudonana exposed to allelopathy such that membranes of living cells became permeable. K. brevis allelopathy appears to target lipid biosynthesis affecting multiple physiological pathways suggesting that exuded compounds have the ability to significantly alter competitor physiology, giving K. brevis an edge over sensitive species.